Implementasi Algoritma RSA (Rivest-Shamir-Adleman) pada Kriptografi Klasik - Muhammad Zaky Zachary; Sisilia Sylviani; Edi Kurniadi (Department of Mathematics, Faculty of Science and Technology Universitas Jambi, 2024)
The implementation of the RSA (Rivest-Shamir-Adleman) cryptography algorithm, which is one of the most commonly used public-key cryptography algorithms. RSA provides high security and is widely used in information security applications such as data encryption, digital signature generation, and key exchange. This research documents the step-by-step implementation process of the RSA algorithm in classical cryptography, including key generation, data encryption, and decryption, leading to the generation of encryption and decryption tables for a specific key.